2020
DOI: 10.1007/s12223-020-00798-1
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of Brucella abortus S19 and other Brucella spp. in the presence of oxidative stress and within macrophages

Abstract: The evolutionary “success” of the genus Brucella depends on the ability to persist both in the environment as well as inside of even activated macrophages of the animal host. For that, the Brucellae produce catalase and superoxide dismutase to defend against oxidative stress. Since the deletion of the mglA gene in the B. abortus S19 vaccine strain resulted not only in an increased tolerance to H2O2 but also in the induction of cytokines in macrophages, we here investigated the effect of oxidative stress (Fe2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In addition to our previous findings about a VBNC phase in Brucella abortus S19 [ 1 ], our results presented here yield further evidence on the formation of a VBNC state in Brucella . The rise of the ATP (RLU-LUMI)/CFU quotients showed that under conditions of different types of oxidative stress (Fe 2+ , H 2 O 2 , bleach), the numbers of colony forming units dropped more quickly with the increase of ATP (RLU-LUMI) values.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition to our previous findings about a VBNC phase in Brucella abortus S19 [ 1 ], our results presented here yield further evidence on the formation of a VBNC state in Brucella . The rise of the ATP (RLU-LUMI)/CFU quotients showed that under conditions of different types of oxidative stress (Fe 2+ , H 2 O 2 , bleach), the numbers of colony forming units dropped more quickly with the increase of ATP (RLU-LUMI) values.…”
Section: Discussionsupporting
confidence: 87%
“…The experiments for testing oxidative stress were carried out in standardized aqueous systems [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Brucella as a facultative parasite possesses more catalase and/or superoxide dismutase (SOD) expression quantity as it needs to resist oxidative stress caused by macrophages. 46 , 47 This reason explains the strong resistance of Brucella to ROS attack.…”
Section: Resultsmentioning
confidence: 99%